Palaearctic Xantholinini of the Museum of Zoology in Lund, Sweden, with description of two new species (Coleoptera, Staphylinidae). 182° contribution to the knowledge of the Staphylinidae - Bordoni, Arnaldo (Zootaxa, 2007)
The European and Mediterranian specimens of the tribe Xantholinini deposited in the Museum of Zoology, Lund, Sweden, were examined. Two new species are described: Phacophallus tuniseus n. sp. from Tunisia (closely related to P. parumpunctatus (Gyllenhal) from Europe), and Xantholinus cypriacus n. sp. from Cyprus. Keys to Mediterranean species of subgenus Calolinus (genus Xantholinus) and Phacophallus are provided. Geonemic data for other 23 species are presented. The following new records are provided: Milichilinus decorus, Leptophius flavocinctus, Hypnogyra angularis, Stenistoderus cephalotes (first record from Bulgaria), Leptophius flavocinctus, Stenistoderus cephalotes, Xantholinus coiffaiti (first record from Corfu), Xantholinus rufipennis (first record from Crete), and X. morandi (first record from Majorca).